Perancangan Proses Kreatif Dalam Mendesain Kostum Dan Menata Make Up Pada Karakter Koboi-Alita - Prabowo, Dayu Amandito; Nafsika, Salsa Solli; Supiarza, Hery (Fakultas Desain Universitas Komputer Indonesia, 2025)
One of the important elements in visuals is artistry, because artistry greatly affects the composition of the resulting image. The main elements of artistic design are costume character design and make-up arrangement. With the concept of costume design and character make-up, a character has its own characteristics in films, TV shows, and stage theatre. The process of making a character in costume and make up design is the main thing to support the deepening of the character, in the making process a case study is carried out and data collection techniques in the form of content analysis, from online media which is then processed in an intensive and detailed way, to explore the process of designing costume and make up characters. after obtaining character design reference data, the data is processed by deeply analysing the acquisition of data that has been obtained. The important impact of research on the process of costume design and styling cowboy character make-up to descriptively describe each process undertaken.